Cancer Malignancy Is Enhanced by Glyceraldehyde-Derived Advanced Glycation End-Products. (28th June 2010) - Takino, Jun-Ichi; Yamagishi, Sho-Ichi; Takeuchi, Masayoshi
Abstract : The receptor for advanced glycation end-products (RAGEs) is associated with the malignancy of cancer. A recent study has suggested that glyceraldehyde-derived AGEs (Glycer-AGEs) enhanced the malignancy of melanoma cells, but glucose-derived AGEs did not. However, the effects of Glycer-AGEs on other cancer cells remain poorly understood, and the molecular mechanisms behind the above-mentioned effect have not been clarified. The present paper aimed to examine the effect of Glycer-AGEs on cultured lung cancer A549 cells. RAGE was expressed in A549 cells. Glycer-AGEs significantly attenuated cell proliferation. Furthermore, Glycer-AGEs enhanced the migration capacity of the cells by activating Rac1 via ROS and also increased their invasion capacity. We demonstrated that Glycer-AGEs enhanced the migration and invasion of A549 cells rather than their proliferation. These results suggest that Glycer-AGEs play a critical role in the malignancy of cancer rather than its proliferation and are potential targets for therapeutic intervention.